Expanding the epigenetic landscape: novel modifications of cytosine in genomic DNA. - Kriaucionis, S; Tahiliani, M (Cold Spring Harbor Laboratory Press, 2014)
Methylation of the base cytosine in DNA is critical for silencing endogenous retroviruses, regulating gene expression, and establishing cellular identity, and has long been regarded as an indelible epigenetic mark. The recent discovery that the ten eleven translocation (TET) proteins can oxidize 5-methylcytosine (5mC) resulting in the formation of 5-hydroxymethylcytosine (5hmC) and other oxidized cytosine variants in the genome has triggered a paradigm shift in our understanding of how dynamic changes in DNA methylation regulate transcription and cellular differentiation, thus influencing normal development and disease.